Maine’s Gubernatorial Candidates Present Their Positions on Health Care Reform - Carter, Jonathan; Collins, Susan; King, Angus (Maine Policy Review, 1994)
Few issues have dominated the public policy agenda in the last decade as health care reform has in 1994. Although health care reform is stalled in Congress at this writing, it is not an issue that will exit the public stage quickly or quietly. Mainefaces many of the problems that have spurred the national health care debate. The state has made some attempts to address these through public policy. But larger health care issues remain unresolved and the next governor will most certainly play a major role in addressing those issues. Maine Policy Review invited the four major candidates seeking to become the state’s next chief executive to present their views on health care reform for publication in this issue. Three of the four candidates, Jonathan Carter, Susan Collins and Angus King, responded to that invitation. Their statements on health care reform are presented in this article